Reflections on disordered growth on urban mobility - Akabane , Getulio K.; Santos, João Almeida; Oliveira, Renata M. N.; Rieder, Romulo (Seven Editora, 2023)
Urban growth is a process of advancement of cities and their respective urban areas, both in size and population growth over time. This process occurs because more and more people decide to move to a certain urban area in search of better living conditions, in search of employment and economic opportunities, services and other benefits that cities can offer. This article aims to present some elements that characterize the effects of disordered urban growth on urban mobility. These elements are based on a bibliographical survey of specific sources that deal with themes such as: urban growth or urbanization, urban dispersion and mobility. The literature review points out that urban sprawl and disorderly growth are directly related and reflected in the decrease in the quality of urban mobility. The research approach is qualitative because it presents the relevant concepts to the theme trying to understand its complexities trying to find a correlation that explains the theme and reaches the objective of this article. Therefore, the bibliographic base is fundamental for the presentation of arguments, analysis and conclusion. In this sense, this article anticipates that the result found shows that urban growth is interdependent on the urban mobility development process, the search for a better quality of life and the cost of living in a part of the city forces people to carry out this trajectory in search of another part of the city where it has lower cost,  job, school, hospital, for example. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-034